2006
DOI: 10.1037/0278-6133.25.6.753
|View full text |Cite
|
Sign up to set email alerts
|

Strategies used in coping with a cancer diagnosis predict meaning in life for survivors.

Abstract: The search for meaning in life is part of the human experience. A negative life event may threaten perceptions about meaning in life, such as the benevolence of the world and one's sense of harmony and peace. The authors examined the longitudinal relationship between women's coping with a diagnosis of breast cancer and their self-reported meaning in life 2 years later. Multiple regression analyses revealed that positive strategies for coping predicted significant variance in the sense of meaning in life-feelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 65 publications
11
87
0
9
Order By: Relevance
“…Considering the psychosocial clinical pathway, we observed that the women in our sample faced breast cancer as a benefit finding event, as has been observed in several other studies [18,44,52,88,89,90], or as posttraumatic growth, which includes: better relationships with family and friends, sense of competence, changes in priorities, greater emotional strength, deeper spirituality and a desire live everyday fully [19,51,52].…”
Section: Resultssupporting
confidence: 76%
“…Considering the psychosocial clinical pathway, we observed that the women in our sample faced breast cancer as a benefit finding event, as has been observed in several other studies [18,44,52,88,89,90], or as posttraumatic growth, which includes: better relationships with family and friends, sense of competence, changes in priorities, greater emotional strength, deeper spirituality and a desire live everyday fully [19,51,52].…”
Section: Resultssupporting
confidence: 76%
“…The search for religion, as a coping strategy in the act of praying, as well as the search for religious services can help to adapt to this new concept of life, in which women can start to see the diagnosis as part of a broader plan that is meaningful for their life, instead of defining it as a random event (21) . Faith plays a significant role as a coping strategy, as belief in God influences the development of adaptive responses to difficult situations deriving from the disease (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Janoff-Bulman,1992). Researchers have identified the cognitive and narrative tasks associated with processing such a diagnosis, drawing attention to the importance of meaning-making around the new situation (Jim et al, 2006;Frank, 1995;Roussi and Avdi, 2008;Bingley et al, 2006). It seems that finding meaning in the experience reduces symptoms of emotional distress associated with the cancer experience (Jim and Andersen, 2007;Tomich and Helgeson, 2002;Voogt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%